Study of the Role of Sex Steroids in the Nodulation of the Thyroid Gland and Uterus (Texas Journal of Medical Science, 2022)
Thyroid function is modulated by genetic and environmental factors, as well as other diseases and drugs such as gonads or sex steroids. The last category of drugs (sex steroids) modulates the activity of the thyroid gland. Gonadal steroids primarily affect thyroid function by altering the clearance of thyroxinebinding globulin (TBG). While estrogen administration leads to an increase in the serum concentration of TBG, androgen therapy leads to a decrease in the level of this binding protein. The influence of gonadal steroids on the clearance and concentration of TCH is modulated by the chemical structure of the steroid used, its chemical structure. This article discusses the role of thyroid sex steroids.